A new approach developed to study variability in North African dust transport routes over the Atlantic during 2001–2015. Issue 19 (9th October 2017) - Meng, L.; Gao, H. W.; Yu, Y.; Yao, X. H.; Gao, Y.; Zhang, C.; Fan, Lei
Abstract: We investigated the variability in the North African dust transport routes over the Atlantic (NAD routes) by extracting the dust transport central axis using Moderate Resolution Imaging Spectroradiometer aerosol data for 2001–2015. The results showed that the NAD routes can be classified into two regimes, a southern route centered at the southernmost position of 6.08 ± 1.12°N during November to March and a northern route centered at the northernmost position of 18.21 ± 1.04°N during April to October. In the southern route, large intervariation was correlated with the Intertropical Convergence Zone (ITCZ) and North Atlantic Oscillation (NAO), but the ITCZ and NAO jointly explained only 38% of the variation. In the northern route, the ITCZ alone explained 67% of the intervariation. The extracted trends during 2001–2015 exhibited a northward shift of 1.68° for the southern route and of 0.52° for the northern route. The causes for the shift were also examined. Key Points: The new approach can well quantify the North African dust transport routes in terms of meridional position and zonal extension The North African dust transport routes over the Atlantic exhibited a northward shift by 1.65° during 2001–2015 The effects of the Intertropical Convergence Zone and the North Atlantic Oscillation on the North African dust transport routes were examined